Does Adapted Self-Exercise Have Benefits for Stiff Shoulders? - Benjawongsathien, Kriangkrai (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Stiff shoulders restrict shoulder motion and affect the quality of life. Several rehabilitation programs have been implemented to improve these conditions. Various exercises have been designed to achieve positive clinical outcomes. However, too many different sets of exercises can confuse patients and lead to infrequent exercises. We aimed to compare the clinical outcomes of a small set of adapted self-exercises to a usual set in patients with stiff shoulders. Methods: Seventy patients with stiff shoulders were randomly assigned to two groups, each performing self-exercises. Self-exercise in group I (the usual set) was composed of ‘wall climbing in front,’ ‘wall climbing at the side,’ and ‘shoulder stretching with a towel,’ and in group II (the adapted set), it was composed of ‘assisted forward flexion stretching in the standing position,’ ‘sleeper stretching in the standing position,’ and ‘doorway or corner stretching.’ The outcome measurements included pain score, functional score, and range of motion. Results: There were no significant differences in the baseline patient characteristics between the groups in terms of sex (p=0.759), age (p=0.521), underlying disease (p=0.322), or body mass index (BMI) (p=0.687). Group II demonstrated significantly higher improvement in mean pain score decrement (-4.5±1.7 vs. -3.5±2.4, p=0.049), mean ASES score improvement (23.1±9.9 vs. 18.3±13.1, p=0.038) and mean degree improvement of shoulder motion in all directions than in group I. Conclusions: The adapted self-exercise set may offer favorable results in treating patients with stiff shoulders and may also be a treatment option for overweight patients.